2022
DOI: 10.1155/2022/3691635
|View full text |Cite
|
Sign up to set email alerts
|

BCKDK Promotes Ovarian Cancer Proliferation and Migration by Activating the MEK/ERK Signaling Pathway

Abstract: Background. Ovarian cancer (OC) is the most fatal gynecologic cancer. The branched-chain α-keto acid dehydrogenase kinase (BCKDK) plays an important role in many serious human diseases, including cancers. Its function in promoting cell proliferation and migration has been reported in various cancers. However, the biological role of BCKDK and its molecular mechanisms underlying OC initiation and progression are unclear. Methods. First, the expression level of BCKDK in OC cell lines or tissues was determined usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…A study conducted by Li et al showed that BCKDK was highly expressed in patients with advanced pathological grade ovarian cancer. This ectopic expression of BCKDK promoted the proliferation and migration of OC cells [199].…”
Section: Amino Acid Metabolismmentioning
confidence: 91%
“…A study conducted by Li et al showed that BCKDK was highly expressed in patients with advanced pathological grade ovarian cancer. This ectopic expression of BCKDK promoted the proliferation and migration of OC cells [199].…”
Section: Amino Acid Metabolismmentioning
confidence: 91%
“…Moreover, BCKDK overexpression promotes ovarian cancer cell proliferation and migration by inducing the MEK/ERK pathway. Accordingly, BCKDK knockdown with shRNAs repressed ovarian cancer cell proliferation and migration in vivo and ex vivo ( 71 ). Transfection of anti- BCKDK siRNA into non-small cell lung cancer cells, including A549, HCC827, and H1299, reduced the expression of BCKDK, decreased BCKDE1α phosphorylation, and inhibited the proliferation of tumor cells in these cancers.…”
Section: Therapeutic Interventionsmentioning
confidence: 99%
“…BCKDK can affect tumorigenesis 6 and distant metastasis 7 in colorectal cancer by regulating the MEK/ERK signaling pathway. BCKDK can promote tumor proliferation and migration in ovarian cancer by activating the MEK/ERK axis 8 . BCKDK knockout in non‐small cell lung cancer can inhibit cancer cell proliferation and accelerate apoptosis 9 .…”
Section: Introductionmentioning
confidence: 99%
“…BCKDK can promote tumor proliferation and migration in ovarian cancer by activating the MEK/ERK axis. 8 BCKDK knockout in non‐small cell lung cancer can inhibit cancer cell proliferation and accelerate apoptosis. 9 Inhibiting BCKDK can increase the cytotoxicity of doxorubicin in triple‐negative breast cancer.…”
Section: Introductionmentioning
confidence: 99%